Online civic engagement: Fostering citizen engagement through social media - Mulyono, Budi; Affandi, Idrus; Suryadi, Karim; Darmawan, Cecep (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The Industrial Revolution 4.0, which makes the internet its backbone, has accelerated the process due to the Covid-19 pandemic which forced citizens to shift all their activities to the digital world, including the involvement of citizens in responding to public discourse. Citizens' public discourses that previously took place in real public spaces have now shifted to digital spaces, one of which is social media. To bridge these changes, a conceptualization of civic engagement is needed through a digital platform. The online citizen involvement was later referred to as online civic engagement, namely civic engagement activities specifically carried out by digital citizens involving several types of digital media, one of which is social media. This literature study provides a clearer picture of the forms of community interaction through social media that go beyond what is known as "slacktivism". When many democracies are faced with the problem of decreasing citizen participation in politics, social media comes with a new form of civic interaction with what is meant by online civic engagement.